Effect of praziquantel treatment of Schistosoma mansoni during pregnancy on intensity of infection and antibody responses to schistosome antigens: results of a randomised, placebo-controlled trial - Tweyongyere, Robert; Mawa, Patrice A.; Emojong, Nicholas O.; Mpairwe, Harriet; Jones, Frances M.; Duong, Trinh; Dunne, David W.; Vennervald, Birgitte J.; Katunguka-Rwakishaya, Eli; Elliott, Alison M. (BMC Infectious Diseases, 2009)
Praziquantel treatment of schistosomiasis during pregnancy was only recommended in 2002; hence the effects of treatment during pregnancy are not fully known. We have therefore evaluated the effects on infection intensity and the immunological effects of praziquantel treatment against Schistosoma mansoni during pregnancy, compared with treatment after delivery.A nested cohort of 387 Schistosoma mansoni infected women was recruited within a larger trial of de-worming during pregnancy. Women were randomised to receive praziquantel or placebo during pregnancy. All women were treated after delivery. Infection intensity after treatment was assessed by a single Kato-Katz examination of stool samples with duplicate slides and categorised as undetected, light (1–99 eggs per gram (epg)), moderate (100–399 epg) or heavy (≥400 epg). Antibodies against S. mansoni worm and egg antigens were measured by ELISA. Results were compared between women first treated during pregnancy and women first treated after delivery.At enrolment, 252 (65.1%) of the women had light infection (median (IQR) epg: 35 (11, 59)), 75 (19.3%) moderate (median (IQR) epg: 179(131, 227)) and 60 (15.5%) had heavy infection (median (IQR) epg: 749 (521, 1169)) with S. mansoni. At six weeks after praziquantel treatment during pregnancy S. mansoni infection was not detectable in 81.9% of the women and prevalence and intensity had decreased to 11.8% light, 4.7% moderate and 1.6% heavy a similar reduction when compared with those first treated after delivery (undetected (88.5%), light (10.6%), moderate (0.9%) and heavy (0%), p = 0.16). Parasite specific antibody levels were lower during pregnancy than after delivery. Praziquantel treatment during pregnancy boosted anti-worm IgG isotypes and to a lesser extent IgE, but these boosts were less pronounced than in women whose treatment was delayed until after delivery. Praziquantel had limited effects on antibodies against egg antigens.S mansoni antigen-specific antibody levels and praziquantel-induced boosts in antibody levels were broadly suppressed during pregnancy, but this was not associated with major reduction in the efficacy of praziquantel. Long-term implications of these findings in relation to resistance to re-infection remain to be explored.
Keywords: Antibody Level; Schistosomiasis; Albendazole; Praziquantel; Infection Intensity